Dichloroacetophenone biphenylsulfone ethers as anticancer pyruvate dehydrogenase kinase inhibitors in non-small cell lung cancer models. (1st June 2023) - Guo, Yizhen; Zhou, Yan; Wu, Puhua; Ran, Maoxin; Xu, Ngai; Shan, Wenying; Sha, Ou; Tam, Kin Yip
Abstract: Pyruvate dehydrogenase kinase 1 (PDK1) is an important metabolic enzyme which is often overexpressed in many types of cancers, including non-small-cell lung cancers (NSCLC). Targeting PDK1 appears to be an attractive anticancer strategy. Based on a previously reported moderate potent anticancer PDK1 inhibitor, 64, we developed three dichloroacetophenone biphenylsulfone ethers, 30, 31 and 32, which showed strong PDK1 inhibitions of 74%, 83% and 72% at 10 μM, respectively. Then we investigated the anticancer effects of 31 in two NSCLC cell lines, namely, NCI–H1299 and NCI–H1975. It was found that 31 exhibited sub-micromolar cancer cell IC50s, suppressed colony formation, induced mitochondrial membrane potential depolarization, triggered apoptosis, altered cellular glucose metabolism, with concomitant reductions in extracellular lactate levels and enhanced the generation of reactive oxygen species in NSCLC cells. Moreover, 31 significantly suppressed the tumor growth in an NCI–H1975 mouse xenograft model, outperforming the anticancer effects of 64 . Taken together our results suggested that inhibition of PDK1 via dichloroacetophenone biphenylsulfone ethers may provide a novel direction leading to an alternative treatment option in NSCLC therapy. Highlights: Dichloroacetophenone biphenylsulfone ether, 31, was developed as PDK1 inhibitor. 31 selectively inhibited PDK1 activity and PDH phosphorylation in NSCLC cells. 31 inhibited NSCLC cell proliferations and suppressed tumor growth in vivo . 31 modulated cell metabolism and Akt-mTOR pathway leading to cancer cell death.